Synthesis and antimicrobial studies of novel derivatives of 4-(4-formyl-3-phenyl-1H-pyrazol-1-yl)benzoic acid as potent anti-Acinetobacter baumannii agents. Issue 3 (1st February 2017) - Allison, Devin; Delancey, Evan; Ramey, Hunter; Williams, Conrad; Alsharif, Zakeyah Ali; Al-khattabi, Hessa; Ontko, Allyn; Gilmore, David; Alam, Mohammad A.
Graphical abstract: Abstract: Microbial resistance to antibiotics is a global concern. The World Health Organization (WHO) has identified antimicrobial resistance as one the three greatest threats for human beings in the 21st century. Without urgent and coordinated action, the world is moving toward a post-antibiotic era, in which normal infections or minor injuries may become fatal. In an effort to find new agents, we report the synthesis and antimicrobial activities of 40 novel 1, 3-diphenyl pyrazole derivatives. These compounds have shown zones of growth inhibition up to 85 mm against Acinetobacter baumannii . We tested the active compounds against this Gram-negative bacterium in minimum inhibitory concentration (MIC) tests and found activity with concentration as low as 4 μg/mL.